The Implementation of Traditional Games to Improve the Social Emotional Early Childhood - Putu Indah Lestari; Elizabeth Prima (Journal of Educational Science and Technology (EST), 2017)
The aims of this study was to improve the social emotional early childhood through the traditional game. This research was conducted on the children of group B TK Pradnyandari III Kerobokan in the academic year 2016 / 2017. This research used Classroom Action Research design with observation method. The subjects of this study were 22 children of  group B1 TK Pradnyandari III Kerobokan consisting of 11 sons and 11 daughters. The object of research is the application of traditional children's games to increase social emotional early childhood. The results og this research as in Cycle I, 14 children (63.64%) reached the completeness learning mastery, 8 children (36.36%) had not reached. In Cycle II, 20 children (90,91%) reached the learning mastery, leaving only 2 children (9,09%) had not reached. The implementation of traditional games can enhance children's social emotional skill. Based on the research findings there was an improvement of 27.27% learning mastery of the children from Cycle I to Cycle II. This means that the application of traditional games can improve children's social emotional development. Traditional games can be piloted in other areas of development skill in early childhood education.